Measuring Employee Performance by Competence and Self-efficacy - Marastika Wicaksono Aji Bawono; Chandra Fitra Arifianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Telecommunication companies that always update themselves, demand optimal employee performance. Increased employee competence can be associated with self-efficacy of self-efficacy in doing work to be able to make increased performance achievements. The purpose of this study was to determine the effect between variables, namely competence, self-efficacy and employee performance. This study uses a quantitative approach using a sample of 206 employees at a telecommunications company. The analytical technique used in this research is path analysis with the help of the partial least square–structural question model (PLS-SEM) program. The results showed that there was an influence between the three variables: competence, self-efficacy and employee performance. Competence affects self-efficacy and employee performance. While self-efficacy affects employee performance and competence affects employee performance through self-efficacy.